Biocontrol Potential of Non-Saccharomyces Yeasts Against Post-Harvest Penicillium Species in Apples and Oranges - Zukisani Gomomo; Morris Fanadzo; Maxwell Mewa-Ngongang; Justin Hoff; Marieta van der Rijst; Lucky Mokwena; Jeremy J. Boonzaier; Rodney S. Hart; Heinrich W. du Plessis (Agricultural Research, 2026)
Fruit producers and exporters around the world are grappling with challenges related to post-harvest fruit decay, particularly in fruits such as apples and oranges destined for export, leading to waste and financial losses. The filamentous fungi, specifically Penicillium species, are the primary post-harvest pathogens affecting apples and oranges. This study evaluated the use of five non -Saccharomyces yeast species ( Suhomyces pyralidae, Meyerozyma guilliermondii, Pichia kluyveri , Zygoascus helenicus and Aureobasidium melanogenum ) as biocontrol agents against Penicillium expansum , P. digitatum and P. italicum . The yeasts were screened for their inhibitory effects using radial inhibition and mouth-to-mouth assays on agar plates and post-harvest trials on apples and oranges. Aureobasidium melanogenum exhibited the most significant growth inhibition in the radial inhibition assay, achieving 60%, 100% and 70% inhibition against P. expansum , P. digitatum and P. italicum, respectively. In the volatile compound assay, Pi. kluyveri achieved complete (100%) inhibition of P. expansum, P. digitatum and P. italicum. Seven volatile compounds were identified, isobutanol, 2-phenylethanol, isoamyl acetate, isoamyl alcohol and 2-phenethyl acetate associated with the inhibition of P. expansum . In post-harvest trials, the yeast treatments displayed limited inhibition activity on apples ( ca. 15%). However, on oranges, M. guilliermondii demonstrated substantial inhibition, achieving 72% and 77% inhibition against P. digitatum and P. italicum, respectively . These findings suggest that the selected yeast species have potential as biological control agents against P. expansum, P. digitatum and P. italicum , although further research is required to fully understand and optimise their application.